2009
DOI: 10.1590/s1413-70542009000200041
|View full text |Cite
|
Sign up to set email alerts
|

Influência do sol nas características fisicas e químicas da tangerina 'Ponkan' cultivada no oeste do Paraná

Abstract: RESUMOA 'Ponkan' (Citrus reticulata Blanco) é uma das tangerinas mais produzidas no Brasil e muita apreciada pelo consumidor brasileiro. Tendo em vista a sua alta aceitação, há preocupação em se produzir frutos de boa qualidade. Entre os fatores que interferem na qualidade dos frutos podemos citar, como exemplo, a radiação solar. Objetivou-se, neste trabalho, avaliar as características físicas e químicas de frutos de tangerina 'Ponkan', cultivados no oeste do Paraná e colhidos em dois quadrantes da planta, um … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 2 publications
0
5
0
10
Order By: Relevance
“…Detoni et al (2009), ao avaliarem a influência do sol nas características físicas e químicas de tangerina 'Ponkan', também observaram que os frutos colhidos no quadrante com maior incidência solar foram os mais pesados.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Detoni et al (2009), ao avaliarem a influência do sol nas características físicas e químicas de tangerina 'Ponkan', também observaram que os frutos colhidos no quadrante com maior incidência solar foram os mais pesados.…”
Section: Resultsunclassified
“…Diversos autores relatam que a composição química dos frutos cítricos é afetada pela posição do fruto na árvore (SITES; REITZ, 1949;REITZ, 1950), cultivar copa e porta-enxerto (ES-PINOZA- NUNEZ et al, 2008), nutrição mineral (DUENHAS et al, 2002), além de fatores climáticos (DETONI et al, 2009).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Cruz et al (2010) found that the tangerine fruit Ponkan, located in the western quadrant of the canopy, presented higher weight values and juice yield than those located in the east quadrant. Detoni et al (2009) observed that the fruits developed in the orientation in which there is a higher incidence of sun, presented higher weight values and a longitudinal diameter. In a similar study, Molin et al (2012) characterised the orange tree yield in a commercial orchard and found the non-occurrence of spatial dependence and large spatial variability in the orchard, as was observed in this study.…”
Section: Spatial Distributionmentioning
confidence: 92%
“…The influence of the sun on the physical and chemical quality of 'Ponkan' tangerines was assessed by Detoni et al (2009), who concluded that the fruit collected in the East-West quadrant of the plant, where more sunlight occurred, had a greater weight and longitudinal diameter. Ramos et al (2003) (Caviglione et al, 2000).…”
Section: Introductionmentioning
confidence: 99%